Reading Peer Review PLOS ONE and Institutional Change in Academia - Paul Eve, Martin (Humanities, 2021)
This Element presents the background contexts and histories of peer review, the data-handling sensitivities of this type of research, the typical properties of reports in the journal to which the authors had access, a taxonomy of the reports, and their sentiment arcs. This title is also available as Open Access on Cambridge Core.